The application of existing statutory provisions in controlling illegal logging activities in Selangor / Cindy Jasmine Enduyan...[et al.] - Enduyan, Cindy Jasmine; Charles, Lovely Natasha; Nik Azlan, Nik Mohd Fadli (2007)
This research aims to find out what are the existing statutory provisions in controlling and illegal logging activities in Selangor and the effectiveness of its application in eradicating this issue. The main act in regulating illegal logging is the National Forestry Act 1984 (amendment 1993) and The National Forestry Policy 1978 (revised 1992). The amendments made to the National Forestry Act in 1993 had changed the forestry management in Malaysia, thus decreasing illegal logging cases as compared to the scenario before the amendments in 1993. Despite the existence of various statutory provisions in curbing illegal logging, it continues due to various reasons which have been thoroughly discussed in this research. There are also bodies and organisations formed in order to curb illegal logging. And for that matter, Malaysia is a producing member of International Tropical Timber Organisation (ITTO). The government plays a crucial role in implementing all the laws that have been enacted.